Uji karakteristik nyala api pembakaran premix bioetanol dari ampas tebu - Saeful Bakhri; Djoko Wahyudi; Alieff Muhammad (TURBO [Tulisan Riset Berbasis Online], 2021)
The fuel demand is very important in this day. The higher fuel consumption was impact depletion of existing reserves of oil resources. Bioethanol is one of the energy conversions from biomass containing sugar, starch and cellulose become fuel. Bagasse is a solid waste containing a lignocellulotic substrate which has the potential for bioethanol production. The purpose of this experiment was to determine the flame characteristics of the composition of the addition bioethanol to Pertamax as a mixture, with a variety of mixtures (B0, B5, B10 and B15). The test was carried out using the premix combustion method. The data from the result experiment were analyzed using descriptive methods. The results of the experiment showed that the addition of bioethanol can affect the flame characteristics. The shape of the flame changes from a conical shape to an enlarged cone angle along with the addition of a percentage. The flame height has decreased, the highest flame is at B0 with value of 12.79 mm, the lowest flame height is at B15 with value 10.27 mm. Combustion velocity has increased, the highest velocity is at B15 with value of 32.753 cm/s and the lowest velocity is at B0 with value of 22.253 cm/s.